0
$\begingroup$

I'm having trouble trying to solve this differential equation: $\frac{dy}{dt} - y = 1 + \cos t$

So far, I've decided:

$\mu(t) = e^{-1\int dt} = e^{-t}$

Which leads me to this:

$e^{-t}\frac{dy}{dt} - e^{-t}y = e^{-t} (1+\cos t)$

$e^{-t}\frac{dy}{dt} - e^{-t}y = e^{-t} + e^{-t}\cos t$

When I begin to integrate the right-hand side, I get:

$e^{-t}y = \int e^{-t}dt + \int e^{-t} \cos t\, dt$

$e^{-t}y = -e^{-t}dt + \int e^{-t} \cos t\, dt$

I'm having trouble integrating the $\int e^{-t} \cos t\, dt$ portion, which makes me think that I'm doing something wrong solving this equation. It seems like integrating it using integration by parts would just lead to an infinite loop of cosine & sine functions.

Am I approaching solving this differential equation incorrectly?

$\endgroup$
2
$\begingroup$

$$ I = \int \mathrm{e}^{-t}\cos t dt = -\mathrm{e}^{-t}\cos(t) - \int \mathrm{e}^{-t}\sin t dt $$

Applying integration by parts again we find $$ \int \mathrm{e}^{-t}\sin t dt = -\mathrm{e}^{-t}\sin t + \int \mathrm{e}^{-t}\cos t\mathrm{e}^{-t}\cos t $$ Putting it all together we find $$ I = \int \mathrm{e}^{-t}\cos t dt = -\mathrm{e}^{-t}\cos(t) - \left[-\mathrm{e}^{-t}\sin t + \int \mathrm{e}^{-t}\cos t\mathrm{e}^{-t}\cos t\right] =-\mathrm{e}^{-t}\cos(t) +\mathrm{e}^{-t}\sin - \int \mathrm{e}^{-t}\cos t dt $$ but the right is just $$ I = \int \mathrm{e}^{-t}\cos t dt = =-\mathrm{e}^{-t}\cos(t) +\mathrm{e}^{-t}\sin t - I $$ re-arrange to find $$ 2I = \mathrm{e}^{-t}(\sin t - \cos t) $$ or $$ I = \frac{1}{2}\mathrm{e}^{-t}(\sin t - \cos t) = \int \mathrm{e}^{-t}\cos t dt $$

$\endgroup$
1
$\begingroup$

Double integration by part works perfectly well .... or use Euler formula

$\int e^{-t} cos t dt=\int e^{-t} \frac {1}{ 2} ( e^{it} + e^{-it})dt=\frac 1 2 \int e^{-t+it} + e^{-t-it})dt=\frac 1 2 \int e^{-t(1-i)}dt + \frac 1 2\int e^{-t(1+i)})dt$

$\endgroup$
1
$\begingroup$

You can also use derivative methods, because: $$(e^{-t}\cos t)'=-e^{-t}\cos t-e^{-t}\sin t$$ and $$(e^{-t}\sin t)'=-e^{-t}\sin t+e^{-t}\cos t$$ thus: $$e^{-t}\cos t=-\int e^{-t}\cos tdt-\int e^{-t}\sin tdt\qquad(1)$$ $$e^{-t}\sin t=-\int e^{-t}\sin tdt+\int e^{-t}\cos tdt\qquad(2)$$ (2)-(1),we'll get it: $$\int e^{-t}\cos tdt=\frac{1}{2}e^{-t}(\sin t-\cos t)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.